Hubungan Dukungan Sosial dengan Kesehatan Mental Remaja di Lingkungan Sekolah - Galuh Nabila Audry Rahmania; Risma Anita Puriani (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescent mental health is a crucial factor in supporting students’ academic success, social interactions, and personal development within the school environment. The various pressures faced by adolescents such as academic demands, developmental changes, and the influence of social and digital environments can increase the risk of mental health issues. Therefore, effective protective factors are needed, one of which is social support. This study aims to examine the relationship between social support and adolescent mental health in the school environment using a qualitative method with a literature review approach. Data were obtained from relevant, openly accessible national journals published between 2020 and 2025. Analysis was conducted using content analysis on 14 articles that met the inclusion criteria. The results of the study indicate that social support has a positive and significant relationship with adolescents’ mental health. Support from family, peers, and teachers has been shown to reduce stress and anxiety levels, as well as improve students’ psychological well-being, resilience, and coping abilities. Conversely, low levels of social support contribute to an increased risk of mental disorders among adolescents. Thus, social support serves as an important protective factor in maintaining and improving students’ mental health. The implications of this study underscore the importance of the involvement of families, schools, and the social environment in building a sustainable support system for adolescents.